Analysis of Human Resources and Infrastructure in Supporting the Learning of Al-Qur'an - Abd Kholid; Indah Tiara Wati; Waslah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Education becomes the first benchmark of a nation's progress. Therefore, currently the Government of Indonesia continues to pursue new breakthroughs in various ways to continue to make learning can continue and develop during the pandemic period both learning innovation, procurement of supporting infrastructure, teaching methods and much more. Openings are only formal education, non-formal education serves to complement the ability of learners by providing learning experiences that are not obtained in school education. Pondok Pesantren Hamalatul Qur'an is a boarding school that prioritizes the learning of the Qur'an. The learning process is packed as tahfidz boarding school in general. As there is a wethon recitation, deposit of the Qur'an on ustadz or ustadzah, madrasatul diniyah, memorize the Qur'an quickly and so on. This research aims to analyze the availability of human resources and facilities and infrastructure in supporting learning activities in boarding schools Hamalatul Qur'an. The research was conducted by observation method, interview and document collection during the research. The results of the research can be the facilities and infrastructure in the boarding school Hamalatul Qur'an and human resources in the boarding school Hamalatul quran and all aspects that support learning activities in boarding schools. This study uses a descriptive qualitative approach.